ANÁLISE DO DESEMPENHO DA EDUCAÇÃO BRASILEIRA BASEADA NOS INDICADORES OFICIAIS PISA E IDEB - Cristina Nunes Rocha (TRF2, 2020)
Pisa is a performance indicator of international basic education that the learning of students from several countries. Idebis a national school performance indicator, applied by INEP. Through Ideb, it is possible to measure whether the goals of the National Education Plan (PNE) are being achieved, as their results serve as a basis for planning and projecting new goals. The aim of this study was to compare the goals projected by the PNE with the results of Pisa and Ideb, with the purpose of understanding the current situation in which basic education is found in Brazil. The study used bibliographic and documentary research and descriptive data analysis as methodology. Initially, the study addressed the characteristics of Brazil that influence education, such as historical factors, population size, illiteracy rate, economy and inequality in income distribution. The analysis period included the results of the Ideb from 2007 to 2017 and the results of the Pisa 2015 and 2018. The study revealed that Brazil has made progress in the universalization of teaching and positive results in early childhood education. However, the final yearsof primary and secondary education have shown low educational levels in Pisa and Ideb and have not achieved the projected goals. The PNE has the challenge of developing actions that promote an inclusive and equitable education, considering the inequalities in education, which are historical in the country